الخطاب الديني في مقررات التعليم الثانوي مضمونه وأهدافه دراسة تحليلية نقدية لمقرر السنة الثالثة ثانوي - خضير, محمد (University of eloued جامعة الوادي, 2015)
إن محتوى الخطاب الديني في مقررات التعليم الثانوي من حيث الدضمون و الأىداف , و كتاب العلوم الإسلامية للسنة الثالثة ثانوي نموذجا عل ذلك ,يتطلب إعطاءه بالغ الاىتمام من حيث صياغة برنامج متكامل مع كافة الأطوار التعليمية الأخرى ,و ندارك نقائصو الدنهجية و الدعرفية و الفنية و الجمالية , و تم تقسيم البحث إلى أربعة فصول : تناول الفصل الأول : ماىية الخطاب الديني خصائصو و أىدافو . و تعرض الفصل الثاني إلى مصادر التربية الإسلامية سماتها الدميزة و أساليبها . أما الفصل الثالث فقد تطرق إلى جملة من النقائص الدنهجية و الدعرفية و الفنية و الجمالية لكتاب العلوم الإسلامية . و تناول الفصل الأخير تفاصيل الدراسة الديدانية لتي تم فيها تحليل و استنتاج إجابة 40 أستاذ بخصوص استمارات الاستبيان . و من أىم النتائج التي توصلت إليها الدراسة ما يلي : - ع دم انسجام ملفات الدنهاج مع الكتاب الددرسي و وجود نقائص منهجية في الدنهاج كما أن عدد الحصص الدقررة لا تكفي لاستيعاب مادة الكتاب . - م ضمون الكتاب يتناسب مع مستوى التلاميذ و مداركهم ,لا يحقق مضامين الكتاب الأىداف الدتوخاة منو ,يتطلب استغلال أرقى الأساليب للتدريس الحديث . - ال طلبة يس ن تعون بالكتاب أثناء الدرس و خارج الحصص الدراسية ,أسلوب الكتاب غير مشوق و لا يحفز التلاميذ على التفكير و البحث و الدشاركة و لا يساعد التلميذ على الاعتماد على نفسو في الفهم . - إ خراج و طبعة الكتاب غير جيدة ,و حجم و خط الكتاب مناسب The religious discourse content in the decisions of secondary education in terms of content and objectives, and a book of Islamic Sciences for the third year secondary model on it, to give him a very requires attention in terms of the formulation of an integrated program with all the other educational stages, and Ndark shortcomings methodology and cognitive and functional and aesthetic , and research is divided into four chapters: The first chapter discusses: what religious discourse characteristics and objectives. Chapter II and subjected to the sources of Islamic education defining characteristics and methods. The third chapter touched on a number of methodological shortcomings and cognitive and functional and the aesthetic of the book Islamic Science. And eating the last chapter of the field study details T-analysis and the conclusion was the answer 40 professor regarding the questionnaire forms. The most important findings of the study include: -Incompatibility of the curriculum files with the textbook and the existence of systematic deficiencies in the curriculum and the number of quotas is not sufficient to accommodate the rule book. -The content of the book commensurate with the level of students and their knowledge, the contents of the book does not achieve the goals envisaged it, it requires the exploitation of the finest modern methods of teaching. -Students Astanon the book during the lesson and outside the classroom, the book is interesting and does not stimulate pupils to think, research, and participation and does not help the student to rely on the same understanding in style. -Output and the book is a good edition, and the size of the book and a suitable line.
ماستر دعوة
Keywords: الخطاب الديني , مقرر التعليم الثانوي , الدنهاج , كتاب العلوم الإسلامية , الوثيقة الدرفقة .; religious discourse, Rapporteur of secondary education, the curriculum, the book of Islamic Sciences, the attached document